PENGGUNAAN ALAT PERAGA SUMPIT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS XII MIPA 2 SMAN 1 PANGKALAN KERINCI - Risnita Risnita (Jurnal Pendidikan, 2018)
This research starts from the low results of learning mathematics students. This can be seen in the daily test of students who are below the Minimum Completion Criteria (KKM). One reason is a low understanding of mathematical concepts. Low understanding of concepts is due to the fact that mathematics is still abstracted by students. Abstract mathematical concepts for students will be easily understood when learning using teaching aids. Learning carried out is direct learning using chopstick props. This study aims to determine the improvement in learning outcomes of students of class XII MIPA 2 SMAN 1 Pangkalan Kerinci and carried out in two cycles consisting of planning, action, observation and reflection. The research data collected is data on learning outcomes and field notes. The collected data was analyzed descriptively. The results of this study indicate that the application of direct learning models using chopstick props can improve learning outcomes. Increased learning outcomes for KD 3.1 amounted to 22.58% or reached 96.77% of students who were above the KKM. While for KD 4.1 the increase from cycle I to cycle II is 22.58% or reaches 93.55% of students are above the KKM.